Miscibility Study of Hexanoyl Chitosan/ Poly(Vinyl Chloride) Blends by Dilute Solution Viscometry and FTIR - H. Muhammad, F.; H.Y. Subban, R.; Winie, Tan (International Journal of Engineering and Technology, 2018)
Miscibility behaviour of hexanoyl chitosan and poly(vinyl chloride) (PVC) blends in different ratios was measured using dilute solution viscometry (DSV) and FTIR spectroscopy. The difference between the experimental and theoretical values of intrinsic viscosity, ∆[η]m and the thermodynamic parameter, α were used to investigate the miscibility behaviour of the blends. FTIR studies suggested that there is no interaction between hexanoyl chitosan and PVC. The values of intrinsic viscosity, ∆[η]m > 0 and α < 0 indicates repulsive interaction and immiscibility of polymer blend. FTIR results for hexanoyl chitosan showed no shift in frequency and no alteration in band shape as well as band inyensity with addition of PVC to the system. Both viscometric and FTIR results showed that hexanoyl chitosan and PVC are immiscible for all compositions under investigation.